Brief Report: Financial Incentives and Real-Time Adherence Monitoring to Promote Daily Adherence to HIV Treatment and Viral Suppression Among People Living With HIV. (1st May 2021) - Bien-Gund, Cedric H.; Ho, Joshua I.; Bair, Elizabeth F.; Marcus, Noora; Choi, Rebekah Ji; Szep, Zsofia; Althoff, Amy; Momplaisir, Florence M.; Thirumurthy, Harsha
Abstract : Background: Interventions to promote medication adherence and viral suppression are needed among HIV-positive individuals. We aimed to determine the feasibility, acceptability, and preliminary impact of daily financial incentives linked to real-time adherence monitoring among treatment-experienced individuals. Methods: At an HIV clinic in Philadelphia, we conducted a pilot randomized trial among treatment-experienced HIV-positive adults with unsuppressed viral loads (>400 copies/mL). Participants randomized to the intervention group were eligible for daily lottery-based financial rewards dependent on antiretroviral therapy (ART) adherence, measured by a wireless-enabled electronic pill bottle. Participants also received a financial incentive for achieving viral suppression at 3 months. The control group received the standard of care. We measured acceptance and feasibility through follow-up survey at 3 months, viral suppression at 3 months, and adherence. Results: Among 29 participants, 28 (93%) completed 3-month follow-up, and 24 (83%) completed a 3-month laboratory visit. Electronic pill bottles were highly acceptable to participants, with most strongly agreeing that they worked well, were reliable, and easy to use. Among those who received the intervention, 77% were very satisfied with their experience. Among those who completed the 3-month laboratory visit, viral suppression was achieved by 40% in the intervention group and 29% in the control group. ART adherence ≥80% was achieved by 36% and 25% in the intervention and control groups, respectively. Conclusions: Daily financial incentives coupled with real-time adherence monitoring are a promising strategy to support ART adherence among HIV-positive individuals who are not virally suppressed. This novel approach warrants testing in a larger trial.